An Empirical Study on the Segmental Features of English Pronunciation of High School Students and Their Impact on Speech Intelligibility - Xiaohu Huang (Universitas Galuh, 2026)
Oral examinations are now part of China’s College Entrance Examination, yet many students lose points due to pronunciation errors that reduce intelligibility, largely stemming from the L1 transfer. High-school instruction seldom targets intelligibility-critical segmental features, partly because these features and their effects are under-researched. To address this gap, researchers analyzed the segmental pronunciation and intelligibility of 55 Grade-10 students in a Chongqing high school. Speech was collected via Voice Memo, annotated by trained raters for segmental errors, and rated for intelligibility; statistical analyses were conducted in IBM SPSS. Results show vowel errors outnumber consonant errors, with certain phonemes (e.g., /iː/, /ɪ/, /θ/) exceeding a 40% error rate. These errors frequently led raters to misidentify words, directly lowering intelligibility scores. Segmental error rates were significantly associated with intelligibility, indicating that targeted training on high-error vowels and consonants can yield measurable gains. The study offers practical guidance for pronunciation instruction, especially in dialect-influenced regions.